Fractional Carbon Dioxide Laser and its Combination with Subcision in Improving Atrophic Acne Scars - Nilforoushzadeh, Mohammad Ali (Adv Biomed Res, 2017)
BACKGROUND: Acne is a very common skin disease in which scars are seen in 95% of the patients. Although numerous treatments have been recommended, researchers are still searching for a single modality to treat the complication due to its variety in shape and depth. We compared the effects of fractional carbon dioxide (CO(2)) laser alone and in combination with subcision in the treatment of atrophic acne scars. MATERIALS AND METHODS: This clinical trial study was performed in Skin Diseases and Leishmaniasis Research Center (Isfahan, Iran) during 2011–2012. Eligible patients with atrophic acne scars were treated with fractional CO(2) laser alone (five sessions with 3-week interval) on the right side of the face and fractional CO(2) laser plus subcision (one session using both with four sessions of fractional CO(2) laser, with 3-week interval) on the left side. The subjects were visited 1, 2, and 6 months after the treatment. Patient satisfaction rate was analyzed using SPSS 20 software. RESULTS: The average of recovery rate was 54.7% using the combination method and 43.0% using laser alone (P < 0.001). The mean patient satisfaction was significantly higher with the combination method than laser alone (6.6 ± 1.2 vs. 5.2 ± 1.8; P < 0.001). Bruising was only seen with the combination method and lasted for 1 week in 57.0% and for 2 weeks in 43.0%. Erythema was seen in both methods. Postinflammatory pigmentation and hyperpigmentation were associated with combination method. No persistent side effects were seen after 6 months. CONCLUSION: Using a combination of subcision and laser had suitable results regarding scar recovery and satisfaction rate.